(untitled) (European Journal of Education and Psychology, 2019)
School absenteeism is a serious problem among youths, varying in etiology and presentation. Youths presenting high levels of absence have previously been linked to mental health problems, academic difficulties and dropout, highlighting the need for early identification and intervention. The aim of this study is twofold: first, to identify profiles among a community sample of secondary school students based on school absence, internalizing and externalizing behavior using the Child Behavior Checklist (CBCL-YSR). Second, to examine the relationship between profiles regarding mental health problems based on the dimensions of the CBCL-YSR, the function of their school absence using the School Refusal Assessment Scale (SRAS) and school refusal using the SChool REfusal EvaluatioN (SCREEN). The profiles are compared on demographic variables, family characteristics, school performance and bullying. A community sample of 469 youths (10-16 year, M=12.1 years, SD=1.2) from six French secondary publics schools participated in this study. Using cluster analysis, four distinct profiles were identified. The clusters differed significantly on school absence, internalizing problems, externalizing problems, dimensions of the CBCL-YSR, and their function of absence on the SRAS. Clusters differed significantly on several demographic variables, school level, grade, repetition and bullying. The distinctions between the four profiles and their relevance are discussed.